Non-therapeutic plasma levels in individuals utilizing curcumin supplements in daily life - Kroon, Maurice A. G. M.; Berbee, Jacqueline K.; Majait, Soumia; Swart, Eleonora L.; van Tellingen, Olaf; van Laarhoven, Hanneke W. M.; Kemper, E. Marleen (Frontiers in Nutrition, 2023)
The spice curcumin and its metabolites are widely used by cancer patients but have not shown proven health benefits in clinical studies, likely due to low plasma concentrations after oral intake. However, public interest in curcumin continues to grow, and companies claim enhanced absorption in their formulations. This study aims to determine if daily oral intake of curcumin leads to sufficient plasma concentrations for health effects. The study was registered in the Dutch Clinical Trial Register with ID NL5931. We used a validated HPLC-MS/MS method to measure curcumin and its metabolites in 47 individuals using their own curcumin formulations. Questionnaires assessed other supplement and medication use. Plasma samples were collected before and 1.5 hours after intake, analyzing curcumin and metabolite levels with and without β-glucuronidase pretreatment to measure conjugated and unconjugated forms. Plasma concentrations of curcumin, demethoxycurcumin, bisdemethoxycurcumin and tetrahydrocurcumin, ranged between 1.0 ng/mL and 18.6 ng/mL. Adding β-glucuronidase resulted in an increase of unconjugated curcumin plasma levels to 25.4 ng/mL; however still significantly below (1000-fold) a plasma concentration that is expected to have a beneficial health effect. The use of adjuvants like piperine did not result in higher curcumin plasma concentrations. Our study shows that using oral curcumin supplements still does not result in therapeutic plasma levels. Health care practitioners need to be critical towards the claimed beneficial systemic health effects of current curcumin supplement use by their patients.